Os efeitos dos mecanismos de transmissão da política monetária no Brasil e no Chile de 1995 a 2010 - Santarossa, Eduardo Trapp (Universidade do Vale do Rio dos Sinos, 2012)
The aim of this study is to investigate how monetary policies are transmitted and their effects in Brazil and Chile. For this purpose, a VEC (vector error correction) model is applied to data running from the first quarter of 1995 to the fourth quarter of 2010 for Brazil and from the first quarter of 2000 to the first of 2011 in Chilean case. Initially, in the review, a theoretical and empirical discussion of the theme is performed. Subsequently, some stylized facts about the monetary policies of Brazil and Chile and other macroeconomic variables for these countries are analyzed. The main results found by the econometric model are that the Brazilian monetary policy may be able to influence economic activity in the long run, and that is a trade-off between increased industrial production and inflation control. Additionally, keeping interest rates at a high level can result in an economic activity downturn, a rising public debt to GDP ratio and an exchange rate appreciation, which has the effect of controlling inflation, but reduces industrial activity. However, the rise in interest rates may be influenced by increases in public debt and risk. The exchange rate showed up as a relevant channel for the transmission of monetary policy, although, not exhibiting long run effects. In Chile, monetary policy seemed to act passively, with industrial production being the most important channel for the deceleration of inflation. The exchange rate has not demonstrated an important role in monetary policy transmission. Furthermore, an increase in interest rates seemed to have greater sensitivity in the fall in industrial activity in relation to the deceleration of inflation, and a long run effect. The low influence of risks in the interest rate may indicate that the Chilean Central Bank can keep this variable in a low base, optimizing its performance.
Keywords: Transmissão de política monetária; Bancos centrais; Mecanismo de correção de erros; Brasil e Chile; Transmission of monetary policy; Central banks; Error correction mechanism; Brazil and Chile; ACCNPQ::Ciências Sociais Aplicadas::Economia